2017
DOI: 10.3126/jgmcn.v10i1.17904
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Measurement of Spleen in Relation to Age: A Prospective Study among Adult Nepalese People in Western Nepal

Abstract: Introduction: Splenomegaly is an enlargement of the spleen which is a quite common problem in any part of the world. Spleen is enlarged in various clinical disorders e.g. infections, metabolism or storage disor­ders and hematological abnormalities. Splenomegaly is an indicator of pathologic process that may be of primary splenic origin but also may be a reflection of disease in virtually any other organ system. Thus, it is important to estimate the splenic size in vivo in the diagnosis, treat­ment and prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 13 publications
(15 reference statements)
2
13
0
Order By: Relevance
“…The sonography assessment of spleen dimensions provides essential inputs for clinicians in daily clinical practice for proper diagnosis of splenomegaly (32,44,(53)(54)(55). The result of this study gives reference values which helps radiologist for appropriate diagnosis of diseases associated to splenomegaly and splenic atrophy, for the surgeons to appropriately design surgical cases associated to spleen, for hematologist and immunologist for proper diagnosis of various gastrointestinal and hematological diseases and forensic studies (56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 96%
“…The sonography assessment of spleen dimensions provides essential inputs for clinicians in daily clinical practice for proper diagnosis of splenomegaly (32,44,(53)(54)(55). The result of this study gives reference values which helps radiologist for appropriate diagnosis of diseases associated to splenomegaly and splenic atrophy, for the surgeons to appropriately design surgical cases associated to spleen, for hematologist and immunologist for proper diagnosis of various gastrointestinal and hematological diseases and forensic studies (56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 96%
“…Despite, spleen length variation, this finding not contradict the clinical guidelines set the upper limit and similar with previous literature which were done in different population. [15][16][17][18] The width of spleen in present study varies from 2.4 cm to 7.3 cm and with mean spleen width of male was 4.6±0.9 cm whereas in female was 4.0±0.6 cm. This finding agreed with African report and study done in Nepal and India.…”
Section: Discussionmentioning
confidence: 99%
“…But, the African report of spleen thickness higher than the present finding. [10,15] The possible reasons for the dimensional variation of spleen may be genetic factors and sociodemographic factors. An ultrasound base study done in an endemic tropical environment reported the mean splenic volume of 202.7 cm3 and 153.7 cm3 in male and female subjects, respectively.…”
Section: Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…However, all splenic dimensional measurements were greater in males than females. [10] Similarly, report from Eastern Nepal indicated that the mean spleen length, width and thickness of male were 9.8±1.18 cm, 4.9±0.9 cm and 3.89±0.62 cm respectively; however, the mean spleen length, width and thickness of female were 9.2±1.26 cm, 4.43±0. [11] cm and 3.46±0.6 cm, respectively.…”
Section: Discussionmentioning
confidence: 99%